Age‐Related Deterioration of Bone Toughness Is Related to Diminishing Amount of Matrix Glycosaminoglycans (GAGs). (18th February 2018) - Wang, Xiaodu; Hua, Rui; Ahsan, Abu; Ni, Qingwen; Huang, Yehong; Gu, Sumin; Jiang, Jean X
ABSTRACT: Hydration status significantly affects the toughness of bone. In addition to the collagen phase, recent evidence shows that glycosaminoglycans (GAGs) of proteoglycans (PGs) in the extracellular matrix also play a pivotal role in regulating the tissue‐level hydration status of bone, thereby affecting the tissue‐level toughness of bone. In this study, we hypothesized that the amount of GAGs in bone matrix decreased with age and such changes would lead to reduction in bound water and subsequently result in a decrease in the tissue‐level toughness of bone. To test the hypothesis, nanoscratch tests were conducted to measure the tissue‐level toughness of human cadaveric bone specimens, which were procured only from male donors in three different age groups: young (aged 26 ± 6 years), mid‐aged (aged 52 ± 5 years), and elderly (aged 73 ± 5 years), with 6 donors in each group. Biochemical and histochemical assays were performed to determine the amount and major subtypes of GAGs and proteoglycans in bone matrix. In addition, low‐field nuclear magnetic resonance (NMR) measurements were implemented to determine bound water content in bone matrix. The results demonstrated that aging resulted in a statistically significant reduction (17%) of GAGs in bone matrix. Concurrently, a significant deterioration (20%) of tissue‐level toughness of bone with age was observed. Most importantly, the deteriorated tissue‐level toughness of bone was associated significantly with the age‐related reduction (40%) of bound water, which was partially induced by the decrease of GAGs in bone matrix. Furthermore, we identified that chondroitin sulfate (CS) was a major subtype of GAGs, and the amount of CS decreased with aging accompanied with a decrease of biglycan that is a major subtype of PGs in bone. The findings of this study suggest that reduction of GAGs in bone matrix is likely one of the molecular origins for age‐related deterioration of bone quality. © 2017 The Authors. JBMR Plus is published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research.